Project Report on Advanced Security System - KIRAN KUMAR, NIRMAL TONY, RAGHVENDRA and SUREKHA A (2006)
INTERNAL GUIDE: SAVITHA, MVJCE EXTERNAL GUIDE: PRAFULL B ROOGI, MAGNUM TECH
Keywords: Advanced Security System